Pertumbuhan Bibit Tanaman Kelor (Moringa oleifera Lam.) Pada Beberapa Macam Media Organik dengan Teknik Pembibitan Tidak Langsung - Rasmani Rasmani; I Gusti Made Arya Parwata; Bambang Budi Santoso (LPPM Universitas Mataram, 2018)
The experimental research is aimed to find out the kind of nursery organic media for better growth of drumstick seedling. It was implemented in January-April 2017 in the nursery field in Dasan Agung, Mataram. The treatments studied were kinds of nursery media including soil media, mixture of soil-sawdust, mixture of soil-cocopeat, mixture of soil-crushed corncobs, mixture of soil-bamboo leaf litter. The experiment design was arranged in a Completely Randomized Design with 5 replications and each content of 5 serial experiment units. The result shows that the kind of seedling media significantly affected the growth to Moringa seedling growth. The soil-cocopeat mixture medium, soil-crushed corn cobs, and soil-bamboo leaf litter were the best medium and more suitable for drumstick seedling compared to soil media and soil-sawdust mixture media